Cu2+-loaded cellulose micro-beads applied to the direct patterning of metallic surfaces using a fast and convenient process. (1st March 2019) - Sèbe, Gilles; Simon, Anne; Dhuiège, Benjamin; Faure, Chrystel
Graphical abstract: Highlights: Cellulose beads were surface-modified by trimellitic anhydride to chelate Cu 2+ ions. Cellulose beads covered by Cu 2+ ions were used to pattern copper surfaces. Hexagonally ordered arrays of copper dots assembled in rings or circles were generated. using electric fields. The distance between copper patterns was controlled by the cellulose micro-beads size. Abstract: In this paper, we propose both a new application for cellulose micro-beads and a new concept in colloidal lithography to directly deposit and template a metal from ions transported by the organized colloidal particles, using the colloidal particles themselves. To do so, 5 μm-sized cellulose micro-beads (CμBs) were first surface-functionalized by trimellitic anhydride to introduce carboxylate ligands before decorating them with Cu 2+ ions by complexation of the carboxylate groups with a CuCl2 solution. The Cu 2+ -loaded CμBs, dispersed in an aqueous phase, were organized in compact monolayer at the vicinity of a planar electrode. The release of cupric ions and subsequent copper deposition were triggered by an electric field delivered by a tension generator. 2D non-close-packing arrays of copper dots assemblies displaying hexagonal symmetry were generated below or around the micro-beads – depending on the ions concentration in the aqueous phase – leading respectively to copper dots deposited circularly or concentrated in rings. The Cu 2+ -loaded cellulose beads allowed the covering of 2 cm²-surfaces by copper patterns in less than 45 min, using an easy and cheap process.